2016
DOI: 10.1002/hep.28267
|View full text |Cite
|
Sign up to set email alerts
|

Novel population‐based study finding higher than reported hepatocellular carcinoma incidence suggests an updated approach is needed

Abstract: Hepatocellular carcinoma (HCC) incidence is rising rapidly in many developed countries. Primary epidemiological data have invariably been derived from cancer registries that are heterogeneous in data quality and registration methodology; many registries have not adopted current clinical diagnostic criteria for HCC and still rely on histology for classification. We performed the first population-based study in Australia using current diagnostic criteria, hypothesizing that HCC incidence may be higher than repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 14 publications
1
68
0
Order By: Relevance
“…Our findings are in line with a recent Australian study estimating the HCC incidence in Melbourne to be 2‐fold higher than reported by CR data, but there are some important differences. Misclassification was a major explanation in the Australian study, only HCC cases with histological verification were classified as HCC (138 in 1 year), the HCCs diagnosed by noninvasive methods and reported to the CR were classified as LCa UNS (123/162 LCa UNS), but about 25% of HCCs were not reported at all.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with a recent Australian study estimating the HCC incidence in Melbourne to be 2‐fold higher than reported by CR data, but there are some important differences. Misclassification was a major explanation in the Australian study, only HCC cases with histological verification were classified as HCC (138 in 1 year), the HCCs diagnosed by noninvasive methods and reported to the CR were classified as LCa UNS (123/162 LCa UNS), but about 25% of HCCs were not reported at all.…”
Section: Discussionsupporting
confidence: 92%
“…Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are both major risk factors for HCC, with an associated 5‐100 fold increased risk of HCC in patients with chronic HBV infection, and a 15‐20 fold increased risk for HCV infection . While previous studies reported that both viral infections account for an estimated 19% of HCC cases in developed countries, a recent prospective epidemiological study from our group indicates that as many as 41% of cases are associated with HCV and 22% of cases are due to HBV infection …”
Section: Introductionmentioning
confidence: 87%
“…We recently reported the first Australian population‐based study of incident HCC 14 . We found that age‐standardised incidence rates of HCC in Melbourne were twice as high as reported by the Victorian Cancer Registry: 10.3 cases (95% confidence interval [CI], 9.0–11.7) per 100 000 men and 2.3 cases (95% CI, 1.8–3.0) per 100 000 women.…”
mentioning
confidence: 85%